Growing ‘Tahiti’ Limes in the Home Landscape - Jonathan H. Crane (EDIS)
This document provides a comprehensive guide on growing 'Tahiti' limes (Citrus latifolia Miller) in home landscapes, covering its scientific background, historical origins, and geographic distribution. 'Tahiti' lime, also known as 'Persian' lime, is believed to originate from southeast Asia and became prominent in the U.S. in the late 19th century. The guide details the climatic adaptations, propagation methods, and planting recommendations for 'Tahiti' lime trees, emphasizing the importance of using disease-free nursery trees and appropriate rootstocks for optimal growth and fruit production. It also highlights the potential challenges posed by diseases like citrus canker and citrus greening. Detailed care instructions, including fertilization schedules and planting techniques for different soil types, are provided to ensure successful cultivation and fruit yield in various environmental conditions. First published in Feb. 1991.